Determinants of Renewable Energy Share in OIC Countries: The Roles of International Financial Flows, Installed Capacity, and Economic Growth - Kholilatul Khusni (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examined determinants influencing renewable energy proportion in Organization of Islamic Cooperation (OIC) countries, focusing on effects of international financial flows, installed renewable electricity capacity, and economic growth. Given the global imperative for energy transition, this research explores how these factors impact renewable energy adoption in nations with diverse socioeconomic contexts. The research used a panel dataset of 50 OIC countries over 23 years. The dependent variable was renewable energy proportion in total final energy consumption, while independent variables included international financial flows for clean energy, installed renewable electricity capacity per capita, and GDP per capita. For robust model specification, econometric methods including Fixed Effects Model (FEM), Random Effects Model (REM), and Hausman test were used. System GMM estimation and Driscoll Kraay standard errors addressed heterogeneity and potential endogeneity. Results show installed renewable capacity per capita has a significant positive impact on renewable energy share, highlighting infrastructure expansion's role in energy transition. International financial flows and GDP per capita showed significant negative effects, indicating financial inflows are not adequately directed towards renewable projects and economic growth remains dependent on fossil fuels. The model accounts for nearly 98% of variation in renewable energy share. The study concludes that direct investment in renewable infrastructure is most effective for promoting adoption, while financial flows and economic growth need stronger alignment with sustainability goals. For OIC countries, successful renewable energy transition depends on channeling resources into green sectors, integrating renewable policies into economic planning, and aligning growth with sustainability.